Progress on the Discovery of Inhibitors of InhA, the FAS II Enoyl-ACP Reductase TB Drug Discovery Targeted on InhA - Zhang, Yi; Xie, Longxiang; Xie, Jianping (Letters in Drug Design & Discovery, 2016)
With ever-increasing drug resistant clinical isolates, novel antibiotics with new targets are urgently needed. Tuberculosis, caused by Mycobacterium tuberculosis, showed formidable antibiotics resistance. InhA, the enoyl-acyl carrier protein (ACP) reductase involved in the type II fatty acid synthesis pathway (FASII) in Mycobacterium tuberculosis, represents an appealing target for the development of new anti-tuberculosis (TB) agents. Inhibitors against InhA might be ideal lead or antibiotics. The latest development of InhA inhibitors is summarized in this paper.
Keywords: tuberculosis